Early written literacy at the end of Grade 2: The impact of handwriting and spelling on quality writing outcomes - Roessingh, Hetty; Nordstokke, David (Language and Literacy / Langue et littératie, 2026)
This inquiry investigates the relationship of the foundational skills of handwriting and spelling as they influence quality writing outcomes at the end of Grade 2 for students of diverse learner profiles. Using trait-based rubrics, expository writing samples for 15 classes (N=298) were scored holistically for quality writing outcomes and secondly, for quality of handwriting. A spelling accuracy rate was calculated, and patterns of spelling errors were recorded. Findings reveal strong connections between fluency of handwriting, spelling and quality writing outcomes for all young learners. We underscore the importance of explicit instruction in handwriting and spelling; and secondly – especially for English language learners (ELLs), attention to vocabulary teaching.